Bioactive decellularized extracellular matrix-based hydrogel supports human adipose tissue-derived stem cell maintenance and fibrocartilage phenotype - Josino, Raphaella; Stimamiglio, Marco Augusto (Frontiers in Bioengineering and Biotechnology, 2024)
Articular cartilage is a highly specialized tissue able to tolerate physical stress. However, its capacity for restoration is restricted, and injuries to the cartilage do not recover spontaneously. Interest in mesenchymal stem cells derived from human adipose tissue (hASCs) is growing due to their potential to improve tissue healing and recovery. Decellularized extracellular matrix (dECM)-based hydrogels combined with hASCs could serve as an interface for studying behavior and differentiation properties in a cartilage microenvironment. In the present study, we described the behavior of hASCs cultured in a commercial dECM MatriXpec™. The structural microtopography of MatriXpec™ was analyzed by scanning electron micrography, and its protein composition was accessed by mass spectrometry. The protein composition of MatriXpec™ is mainly represented by collagen proteins, building its fibrous ultrastructure. hASCs were cultured three-dimensionally (3D) on MatriXpec™ to perform cell viability, growth, and cartilage differentiation analysis. We showed that MatriXpec™ could be loaded with hASCs and that it supports cell maintenance for several days. We observed that the threedimensional ultrastructure of the biomaterial is composed of nanofibers, and its protein composition reflects the tissue from which it was harvested. Finally, we showed that the molecular cues from the hydrogel are biologically active as these influence cell behavior and differentiation phenotype, increasing the expression of fibrocartilage-related genes such as SOX9, COL1, COL10, and MMP13. MatriXpec™ hydrogel can be used as an interface for 3D hASCs culture studies as it maintains cell viability and supports its differentiation process.